5(v-3)-2v=-30

Simple and best practice solution for 5(v-3)-2v=-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(v-3)-2v=-30 equation:


Simplifying
5(v + -3) + -2v = -30

Reorder the terms:
5(-3 + v) + -2v = -30
(-3 * 5 + v * 5) + -2v = -30
(-15 + 5v) + -2v = -30

Combine like terms: 5v + -2v = 3v
-15 + 3v = -30

Solving
-15 + 3v = -30

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 3v = -30 + 15

Combine like terms: -15 + 15 = 0
0 + 3v = -30 + 15
3v = -30 + 15

Combine like terms: -30 + 15 = -15
3v = -15

Divide each side by '3'.
v = -5

Simplifying
v = -5

See similar equations:

| 10x^8=40 | | (3x-5)(3x+4)= | | 5+22a=2+.45 | | 17+5n/4= | | 2x-4=2x+3 | | 1/3(x-8)=10 | | x/4-5/3=1/12 | | x^2-9x-5=-5x | | 5(2d+4)=36 | | 8y+4(8+y)=3(y-3)+10y | | 5x+98=2 | | -5b=7b | | (8x+6)/12=(3x/5)+2 | | 6/5x-3/5x=-7/3-4/3 | | 1/3x+2/4x+x+18+x+60+2x=540 | | -4x-12=16 | | -140/8-20/8=x | | 2x-(6x-2)=1 | | r=r+5 | | l=7(3.14)r | | 3g+11-5g=17 | | 11x-8+4x+x+7= | | 3x^2+2x-3x^2+9= | | 2(x-2)+3x=-3(2x+1) | | .25(16+4t)-.5(10+2t)= | | -7x=4x+62 | | 2x^2-x^4-1=0 | | 7x=4x+62 | | x(5x-9)=(5x+9)(x-3) | | (-76)+(-37)-38+(-60)= | | 2(2h+1)+3(4h+7)= | | -2/3+(-7/2) |

Equations solver categories